The Ugly Truth Behind Shell PLC: Reaping Record Profit by Greenwashing - ERBUĞA, Gökçe Sinem; Atağan, Gülşah (International Journal of Contemporary Economics and Administrative Sciences, 2024)
British oil giant Shell plc is often associated with scandals. The company’s bad reputation began in 2004 by inflating its existing reserves. While the previous scandal hasn’t been forgotten yet, it caused an unprecedented environmental disaster in Nigeria. Shell, which attaches great importance to environmental concerns on paper, cannot give a good test in practice. This research examines the concept of greenwashing examined with a special emphasis on Shell. In this study, evidence regarding the greenwashing activities carried out by the Shell was presented and it was aimed to determine the effect of greenwashing activities behind the company’s record profit.